Identifying the Power of Social-Emotional Literacy for Students in Filtering Religious Information in the Digital Era - Zulmi Ramdani; Indah Wigati; Yuniar; Baharudin (Cendekia: Kependidikan dan Kemasyarakatan, 2026)
The digital era has significantly influenced the dissemination and filtering of religious information. This study aims to analyze students' social-emotional literacy in filtering religious information in the digital era. This type of research is descriptive quantitative. The research instrument consisted of 22 statements based on indicators of self-awareness, self-management, responsible decision-making, relationship skills, and social awareness. Respondents in this study were 179 students at the Islamic College of Palembang. All data obtained were analyzed using percentages. The research results indicate that students have a strong ability to filter religious information, particularly in self-management and decision-making. However, obstacles remain, including limited digital literacy, digital environmental disruption, and a lack of guidance in providing information. This research emphasizes the importance of strengthening socio-emotional literacy through education and a supportive learning environment to enable students to think critically, verify information accurately, and adopt a wise and tolerant approach to the flow of religious information in the digital era.